2018
DOI: 10.1177/1077801218815778
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Gender-Based Violence Among Adolescents and Young Adults: Lessons From 25 Years of Program Development and Evaluation

Abstract: Effective prevention of intimate partner violence (IPV) among adolescents and young adults is a key strategy for reducing rates of gender-based violence (GBV). Numerous initiatives have been developed and evaluated over the past 25 years. There is emerging evidence about effective strategies for universal prevention of dating violence in high school settings and effective bystander interventions on university and college campuses. In addition, there have been some effective practices identified for specific gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 85 publications
(106 reference statements)
0
118
0
3
Order By: Relevance
“…Education and learning are key factors in GBV prevention (Crooks et al 2019). The UN Women's report on the transformative potential of Agenda 2030 for gender equality highlights the importance of women's and girls' educational levels in advancing the goal of gender equality, which involves overcoming all forms of violence against women.…”
Section: Interactive Learning Environments To Prevent Gender-based Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Education and learning are key factors in GBV prevention (Crooks et al 2019). The UN Women's report on the transformative potential of Agenda 2030 for gender equality highlights the importance of women's and girls' educational levels in advancing the goal of gender equality, which involves overcoming all forms of violence against women.…”
Section: Interactive Learning Environments To Prevent Gender-based Violencementioning
confidence: 99%
“…(Brännström et al 2017). Along these lines, several studies revealed a greater risk of suffering from gender-based violence (GBV) (Crooks et al 2019;Wolfe et al 2003). GBV is considered one of the most significant current social concerns, not only because of its higher occurrence but also because of its increasing prevalence at younger ages and the fact that it negatively affects the mental and physical health of many victims (Adhia et al 2019;Puigvert et al 2019;Racionero-Plaza et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Education of youths, sensitization of victims to lodge a complaint, political engagement and justice could contribute to reduce gender-based violence. Crooks and al prevention of intimate partner violence among adolescents and young adults is a key strategy for reducing rates of gender-based violence (Crooks et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, how does the underlying behavioral change necessary to address the reduction of risk become encouraged and ultimately enforced across multiple areas, such as individuals, societies, and institutions? Ideally, programming needs to promote personal and collective thought and enable activism and community action across different levels to work towards attaining gender equality (Michau et al 2015;Flood 2015;Crooks et al 2019). Spangaro et al (2013) found in their evaluation of various initiatives to reduce risk and incidence of sexual violence that there was no "one-size-fitsall" approach with the diversity of situations and histories surrounding gender inequality and violence in the culture and multiple strategies needed to adequately address the complexity of needs across different levels of societies.…”
Section: Reducing Sexual Violence: Prevention and Survivor Servicesmentioning
confidence: 99%
“…These activities ensure that students who are victims or at risk of violence have appropriate support and access to child-and adolescent-friendly services. An example of the outcomes used to evaluate individual and community interventions: (Barker et al 2011;Casey et al 2013;Chakraborty et al 2018;Fulu et al 2013;Peacock and Levack 2004;Lundgren and Amin 2015;Crooks et al 2019;CARE 2013;Mills et al 2015;Slegh and Richters 2012). A few of the most recognized campaigns and programs include:…”
Section: Transformative Community-based Social Change Programsmentioning
confidence: 99%